2000
DOI: 10.1177/1071557600007001s10
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Action and Cross-Talk Between Estrogen Receptor and Progesterone Receptor Pathways

Abstract: The intriguing biology of estrogens and progestins in their diverse target cells is determined by the structure of the hormonal ligand, the receptor subtype or isoform involved, the nature of the hormone-responsive gene promoter, and the character and balance of coactivators and corepressors that modulate the cellular response to the receptor-ligand complex. Estrogens regulate the growth, differentiation, and functioning of diverse target tissues, both within and outside of the reproductive system. Most of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
37
1
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 26 publications
3
37
1
1
Order By: Relevance
“…One possibility is that the ratios of the two hormones in this group may be at a threshold level, allowing progesterone to antagonize the estradiol effect on susceptibility in some mice and not in others. This phenomenon of situation-dependent antagonism of estradiol effects by progesterone is well recognized (11). Other examples where progesterone by itself does not appear to regulate an immune function but does clearly interfere with estradiol effects have been documented (13,33).…”
Section: Discussionmentioning
confidence: 97%
“…One possibility is that the ratios of the two hormones in this group may be at a threshold level, allowing progesterone to antagonize the estradiol effect on susceptibility in some mice and not in others. This phenomenon of situation-dependent antagonism of estradiol effects by progesterone is well recognized (11). Other examples where progesterone by itself does not appear to regulate an immune function but does clearly interfere with estradiol effects have been documented (13,33).…”
Section: Discussionmentioning
confidence: 97%
“…Steroid hormones often have antagonist effects that are not equal in all (mammalian) cell types (4,5,25,49). In this regard, there are at present very limited data describing the response(s) of (primary) cervical epithelial cells to combined, variable physiological concentrations of estrogens and progestagens-such as would occur in vivo throughout the female menstrual cycle-or how these responses potentially might be altered during bacterial infection.…”
Section: Discussionmentioning
confidence: 99%
“…It will be interesting to determine the molecular fingerprints of these adjacent neurons. Within individual neurons, PR-B also may be regulating the downregulation of ERa in the VMN, an effect that, in vitro, is mediated by both PR-A and PR-B in a ligand and cell-specific manner (DonCarlos et al 1995, Katzenellenbogen 2000. Previous protein and mRNA studies have shown such a role for PR in other reproductive tissue (Ismail et al 2002).…”
Section: Discussionmentioning
confidence: 99%